Business Plan : World of Banana / Ahmad Hazim Sobri … [et al.] - Sobri, Ahmad Hazim; Mohd Basri, Nor Ayuni; Nasaruddin, Noranisya; Ludin, Nur Athira; Hassan, Nor Nadia (2021)
The product we choose to sell is grilled banana. “World of Banana Company” was established on early year of 2020. The grilled banana industry in Malaysia is still not popular despite the high demand for grilled bananas. Currently, there are very few restaurants in Malaysia that sell grilled bananas. This is because most restaurants in Malaysia only make fried bananas, so we have made a difference by roasting the bananas because the product has gone viral abroad and there is a lot of demand from the public. Therefore, we think that this is a good opportunity for us to be involved in the business of making grilled bananas because we can supply our products to all customers. There are several factors why we choose to grow this business. The first is that the making of grilled banana is still not many people make it, so we took the opportunity to sell grilled banana in Kota Bharu Kelantan because in Kelantan there is no restaurant that sells grilled banana. The second reason is that this grilled banana has been in high demand so this is our opportunity to introduce the product and can provide many benefits to our company. The reason why we chose to sell this grilled banana is because, most people in Malaysia only sell fried bananas and we agreed to give a difference by selling grilled banana because there is a lot of demand by the public but there are still no or few stores that sell grilled banana. So, we took this opportunity by selling grilled bananas in order to get an amazing response and earn a lot of profit. Moreover, we hope that our business continues to grow and hope that our branches can be opened all over Malaysia